Omega bankruptcy for different Lévy models - Kaszubowski, Adam (Bankructwo typu Omega dla różnych modeli Lévy’ego, 2019)
In this paper, we consider the so-called Omega bankruptcy model, which can be seen as an alternative to the classical approach to ruin. In contrast to the classical model, we allow the process to go below the level zero, however not further than some fixed level −d<0. In addition, when the process is below zero it can be killed with some intensity function ω. Our aim is to show the relations between the Omega model and classical ruin for two important Lévy models, i.e. we consider the Crámer-Lundberg process and the Markov modulated Brownian motion. We also provide numerical experiments to confirm obtained analytical results
Śląski Przegląd Statystyczny = Silesian Statistical Review, 2019, Nr 17 (23), s. 31-57
Keywords: ruin probability; Omega model; Cramer-Lundberg process; Markov modulated Brownian motion; prawdopodobieństwo ruiny; model Omega; proces Cramera-Lundberga; markowsko modulowany ruch Browna